2017
DOI: 10.3382/ps/pew386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary organic zinc and α-tocopheryl acetate supplements on growth performance, meat quality, tissues minerals, and α-tocopherol deposition in broiler chickens

Abstract: The aim of this study was to evaluate the effects of different dietary levels of zinc (Zn) and α-tocopheryl acetate (α-TOA) on broilers performance, meat quality, Zn, selenium (Se), and α-tocopherol (α-TO) tissue depositions. A total of 1,080 one-day-old Ross 308 broiler chickens (mixed-sex) were allocated to nine dietary treatments. Three levels of supplemental Zn (0, 60, and 120 mg/kg of diet) and three levels of α-TOA (0, 150, and 300 mg/kg of diet) were combined as a completely randomized design with 3 × 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Frozen thigh and breast samples (right sides of the carcass) were trimmed to 2 cm × 1 cm × 1 cm (length × width × thickness), placed in a plastic bag and fastened to avoid evaporation and left at 4 °C, and the final weight was determined at 24 h postmortem. Percentage of drip loss was calculated by 100 × (initial muscle weight – final muscle weight/initial muscle weight) as described by Akbari Moghaddam Kakhki et al. (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen thigh and breast samples (right sides of the carcass) were trimmed to 2 cm × 1 cm × 1 cm (length × width × thickness), placed in a plastic bag and fastened to avoid evaporation and left at 4 °C, and the final weight was determined at 24 h postmortem. Percentage of drip loss was calculated by 100 × (initial muscle weight – final muscle weight/initial muscle weight) as described by Akbari Moghaddam Kakhki et al. (2017).…”
Section: Methodsmentioning
confidence: 99%
“…At 24-h postmortem, right side of breast and thigh muscles were used for pH measurement using a pH meter (model 691 Laboratory pH Meter, Metrohm Co, Herisau, Switzerland) instrument at a depth of 2.5 cm below the surface, as described by Akbari Moghaddam Kakhki et al. (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Contrasting results were found by Kakhki, Bakhshalinejad, Hassanabadi and Ferket (2017), who evaluated the effect of three levels of alpha-tocopherol acetate (0, 150 and 300 mg / kg of food) and three levels of zinc (0 , 60 and 120 mg / kg of feed) on performance, meat quality and the amount of zinc, selenium and alpha-tocopherol in the breast and thigh muscle and liver of broilers. The authors noted that zinc and alphatocopherol acetate did not influence carcass performance or yield parameters; however, alpha-tocopherol and zinc supplementation increased alpha-tocopherol deposition in the liver, chest and thigh.…”
Section: Introductionmentioning
confidence: 75%
“…The significant increase in zinc concentration in both liver and brain tissues of ZnO-NP-treated Japanese quails compared to the control confirmed that tissue mineral biodistribution can be used as an index of mineral storage in the body [ 37 ]. Previous works indicated that Zn levels in the liver and other tissues were significantly increased by dietary inclusion of Zn either in the form of zinc oxide [ 40 ] or nano-zinc oxide [ 41 ] in broiler chickens. The retention of zinc in either liver or brain tissue was dose independent.…”
Section: Discussionmentioning
confidence: 99%